Do expert reviews really drive demand? Evidence from a German car magazine - Ralf Dewenter; Ulrich Heimeshoff (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2014)
A wide range of media provide information on many products based on reviews or expert opinions. A natural question is, whether these reviews and expert opinions have any effect on sales. A small but growing literature in economics and marketing science deals with this issue, by testing the relevance of such product information for goods such as financial instruments, wine, books and movies. However, most of these products have in common that quality is very difficult to measure. It is always also a matter of taste whether these products can be seen as high or low quality goods. Based on a unique dataset, we test whether test scores published in a major German car magazine have significant impact on registrations of new cars in Germany. We find that test scores for certain cars have statistically significant impact on the number of new cars sold by several leading manufacturers on the German car market.
Keywords: L15; L82; 330; Car magazines; Test Scores; Demand